If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2.1 + -14y = -5.9 + -1(8y + -2) Reorder the terms: 2.1 + -14y = -5.9 + -1(-2 + 8y) 2.1 + -14y = -5.9 + (-2 * -1 + 8y * -1) 2.1 + -14y = -5.9 + (2 + -8y) Combine like terms: -5.9 + 2 = -3.9 2.1 + -14y = -3.9 + -8y Solving 2.1 + -14y = -3.9 + -8y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '8y' to each side of the equation. 2.1 + -14y + 8y = -3.9 + -8y + 8y Combine like terms: -14y + 8y = -6y 2.1 + -6y = -3.9 + -8y + 8y Combine like terms: -8y + 8y = 0 2.1 + -6y = -3.9 + 0 2.1 + -6y = -3.9 Add '-2.1' to each side of the equation. 2.1 + -2.1 + -6y = -3.9 + -2.1 Combine like terms: 2.1 + -2.1 = 0.0 0.0 + -6y = -3.9 + -2.1 -6y = -3.9 + -2.1 Combine like terms: -3.9 + -2.1 = -6 -6y = -6 Divide each side by '-6'. y = 1 Simplifying y = 1
| 3(x-5)+4(2x-1)=47 | | x+6+5x-12+7x-48=180 | | 9/4*9 | | 4x^2+10x-143=0 | | 3p-q=9 | | 1700j+140=4500 | | 0.2(x+30)*.6x=22 | | 24-6=45-90 | | 9/10-2/5= | | 2(x+30)+6x=22 | | x^2-10x+15=-10 | | x+4+4x-8+7x-35=180 | | 0.33333333x+-3=3 | | -0.18/t=-5.2 | | 9x+2+13x-18+17x+1=180 | | 12=z/-9 | | 0=10x^4-24x^3-3x^2 | | 3.2x+6=15 | | x/7+5=-2 | | x/18=2 | | Y-1=X-3 | | 4x-3+9x-6+6x-1=180 | | 8(5-x^2)-3= | | z/7+9=5 | | X^4-13x^3+36= | | 6t-.16666667=9 | | 3(X+1)-2(X-2)=5 | | 18/48 | | 2/5-2/10 | | 5x-4+3=9-x | | -39+x^2=10x | | 42-21x+252=44 |